Photobiomodulation therapy applied during an exercise-training program does not promote additional effects in trained individuals: A randomized placebo-controlled trial - Machado, Aryane F. [UNESP] (2022)
Background: Previous studies have shown positive results of photobiomodulation (PBM) for improving performance and accelerating post-exercise recovery. However, the effects of PBM in healthy individuals who underwent a neuromuscular adaptation training remain unclear. Objective: To investigate the effects of PBM during a training program combining sprints and explosive squats exercises on clinical, functional, and systemic outcomes in trained healthy individuals compared to a placebo intervention and a control. Methods: We conducted a randomized placebo-controlled trial. Healthy males were randomly assigned to three groups: active PBM (30 J per site), placebo, or control (passive recovery). The participants performed a six-week (12 sessions) of a training program consisting of a combination of sprints and squats with recovery applied between sprints and squats. To prevent the influence of the primary neuromuscular adaptation to exercise on the results, all participants had to participate in a period of six weeks of exercise training program. Functional, clinical, and psychological outcomes and vascular endothelial growth factor (VEGF) were assessed at baseline and after six weeks. Results are expressed as mean difference (MD) and 95% confidence intervals (CI). Results: Thirty-nine healthy male volunteers (aged 18–30 years; body mass index 23.9 ± 3 kg/m²) were recruited. There was no significant time by group interaction, and no significant effect of group, but there was a significant effect of time for maximal voluntary isometric contraction (primary outcome) (MD=22 Nm/kg; 95%CI: 3.9, 40) and for squat jump (MD=1.6 cm; 95CI%: 0.7, 2.5). There was no significant interaction (time*group), time, or group effect for the other outcomes. Conclusion: The addition of PBM to a combined training performed for six weeks in previously trained individuals did not result in additional benefits compared to placebo or no additional intervention.